Iron Deficiency Anemia and Vitamin D Deficiency in Female patients presenting to OPD in Sialkot - Khudija Bibi, Asifa Ashraf, Bukhtawar Akber, Momin Ali Baber, Barkat Ali Babar, Saleh Ehsan, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the relation of iron deficiency anemia and level of vitamin D in healthy females and diseased group Methods: A cross sectional study with convenient sampling was done having iron deficiency anemia and low level of Vitamin D in females. Total subjects were n= 90 group A has iron deficiency anemia and low level of vitamin D and Group B is control group comprised normal female. Results: We collected blood from all subjects from antecubital vein. Blood is analyzed for Hb and Hematocrit percentage. Serum was separated to determine the level of Vitamin D & serum ferritin. Conclusion: It is observed that hemoglobin, hematocrits, serum Ferritin and vitamin D levels were lower in the diseased group when compared with the healthy females with P value of < 0.001.